Association of microcirculation, macrocirculation, and severity of illness in septic shock: a prospective observational study to identify microcirculatory targets potentially suitable for guidance of hemodynamic therapy - Sturm, Timo; Leiblein, Julia; Schneider-Lindner, Verena; Kirschning, Thomas; Thiel, Manfred (Journal of intensive care medicine, 2016)
Purpose:Clinically unapparent microcirculatory impairment is common and has a negative impact on septic shock, but specific therapy is not established so far. This prospective observational study aimed at identifying candidate parameters for microcirculatory-guided hemodynamic therapy.ClinicalTrials.gov:NCT01530932.Materials and Methods:Microcirculatory flow and postcapillary venous oxygen saturation were detected during vaso-occlusive testing (VOT) on days 1 (T0), 2 (T24), and 4 (T72) in 20 patients with septic shock at a surgical intensive care unit using a laser Doppler spectrophotometry system (O2C).Results:Reperfusional maximal venous capillary oxygen saturation (SvcO2max) showed negative correlations with Simplified Acute Physiology Score II (SAPSII)/Sequential Organ Failure Assessment (SOFA) score, norepinephrine dosage, and lactate concentration and showed positive correlations with cardiac index (CI). At T24 and T72, SvcO2max was also inversely linked to fluid balance. With respect to any predictive value, SvcO2max and CI determined on day 1 (T0) were negatively correlated with SAPS II/SOFA on day 4 (T72). Moreover, SvcO2max measured on day 1 or day 2 was negatively correlated with cumulated fluid balance on day 4 (r= ?.472, P < .05 and r = ?.829, P < .001). By contrast, CI neither on day 1 nor on day 2 was correlated with cumulated fluid balance on day 4 (r = ?.343, P = .17 and r = ?.365, P = .15).Conclusion:In patients with septic shock, microcirculatory reserve as assessed by SvcO2max following VOT was impaired and negatively correlated with severity of illness and fluid balance. In contrast to CI, SvcO2max determined on day 1 or day 2 was significantly negatively correlated with cumulative fluid balance on day 4. Therefore, early microcirculatory measurement of SvcO2max might be superior to CI in guidance of sepsis therapy to avoid fluid overload. This has to be addressed in future clinical studies.
Gesehen am 24.04.2019